A Pan-Cancer Analysis of the Oncogenic Role of Integrin Beta4 (ITGB4) in Human Tumors - Huang W; Fan L; Tang Y; Chi Y; Li J (International Journal of General Medicine, 2021)
Wenjie Huang,1,* Li Fan,1,* Yongmei Tang,1 Yinxiu Chi,2 Jingjing Li1 1Department of Reproductive Medicine, Liuzhou Maternity and Child Healthcare Hospital, Affiliated Women and Children’s Hospital of Guangxi University of Science and Technology, Liuzhou, Guangxi, 545001, People’s Republic of China; 2School of Basic Medicine, Central South University, Changsha, Hunan, 410078, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jingjing Li; Wenjie Huang Email 7407lijingjing@163.com; a17377552242@163.comBackground: Integrin beta4 (ITGB4) is a transmembrane receptor that plays a key role in tumorigenesis and tumor development. However, there are no pan-cancer analyses of ITGB4.Methods: This study demonstrates the first potential oncogenic roles of ITGB4 across 33 tumors based on the dataset of the Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO).Results: ITGB4 is highly expressed in many cancers, and distinct correlations exist between ITGB4 expression and the prognosis of tumor patients. We also found that the methylation and genetic alteration level of ITGB4 was associated with some cancer prognosis. Furthermore, we found a reduced phosphorylation of ITGB4 at S1457 in several tumors, such as breast and ovarian cancers. Finally, ITGB4 expression was correlated with cancer-associated fibroblasts in liver hepatocellular carcinoma and prostate adenocarcinoma, and the infiltration level of NK cells and neutrophils was observed in other cancers, such as breast invasive carcinoma and lung adenocarcinoma. Moreover, RNA metabolism and protein processing-associated functions are involved in the functional mechanism of ITGB4.Conclusion: Our first pan-cancer study may offer a relatively comprehensive understanding of the oncogenic roles of ITGB4 across different tumors.Keywords: ITGB4, cancer, prognosis, methylation, phosphorylation